Menganalisis Interpretasi Putus Cinta Mahasiswa Marketing Communication BINUS LE51 melalui Percakapan di WhatsApp - Christy, Levina; Rhamaniya, Anak Agung Ayu Tirta; Purwoko, Keysha Athaya; Gunawan, Aloysius Bernanda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This journal aims to understand how Marketing Communication students from Binus LE51 interpret the experience of a breakup through conversations on the WhatsApp application. Using a qualitative descriptive method with a hermeneutic interpretation approach, the research analyzes conversation content from five students who voluntarily shared their breakup experiences. The study also found that the emotional recovery time after a breakup varies, depending on the closeness of the previous relationship and the support from friends. The study suggests the importance of further exploring the role of social media in emotional recovery processes among students, particularly within the increasingly interconnected digital environment. The end of a romantic relationship significantly impacts students' mental health and academic performance. Through a qualitative approach, the study reveals that breakups often trigger negative emotions such as sadness, anxiety, and stress. These emotions lead to decreased concentration, reduced quality of assignments, and poor academic performance.